Protective roles of flavonoids and flavonoid-rich plant extracts against urolithiasis: A review. Issue 13 (20th July 2019) - Zeng, Xiangquan; Xi, Yu; Jiang, Weibo
ABSTRACT: In the urinary system, urolithiasis is the third prevalent disorder which causes severe pain in individuals. Urinary stones are composed of calcium oxalate (CaOx) and calcium phosphate in approximately 80% of patients. Although various drugs and surgery operations are used to treat the disease, side effects of drugs and the high recurrence after therapy in patients cannot be ignored. Flavonoids are a large group of plant polyphenols with presumed beneficial effects on several common diseases. Whereas, a very few have reached clinical use. The results of recent studies have shown that the plant flavonoids could effectively inhibit the formation of CaOx stones in vitro and in vivo, correlating with their diuretic, antioxidant, anti-inflammatory, antibacterial properties and other protective effects. Thus, the flavonoids or flavonoid-rich plant extracts endowed with anti-urolithiasis activities and probable mechanisms of actions were reviewed. In addition, we also put forward some issues needed to be concerned in future investigations as well as offered prospects and challenges for developing the plant flavonoids into drugs for stone prevention.